(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The aim is to introduce and identify the main barriers and perceived risks associated with active transportation to and from school in a city level initiative in Olomouc, Czech school-aged children. Methods: The Olomouc city introduced a project ‘Safe Road to School’ in 2018 to all city schools. The main objective of the project was to identify dangerous places and thus prevent traffic accidents where children are moving and to minimise the risk of their occurrence. Map application, aimed at 4/5 and 8/9 graders, was applied to identify problematic or dangerous areas and their gradual removal. The presentation provides an overview of the main barriers identified within three rounds of this initiative in 2019, 2021, and 2023. Results: Most children reported walking as their primary mode of transportation to (58% in 2019, 45% in 2021, and 55% in 2023) and from school (63% in 2019, 50% in 2021, and 58% in 2023), primarily due to perceived safety (83% in 2019, 85% in 2021, and 79% in 2023). The main safety concerns identified were speeding traffic (36% in 2019, 37% in 2021, and 38% in 2023). The school neighbourhood was often perceived as safe, with some issues of unpleasant and unsafe episodes due to the presence of homeless individuals, alcohol users, missing crosswalks, and speeding cars. Experience with these findings indicate the awareness of authorities to solve the issue as soon as possible. Conclusion: All alerts recorded by the pupils on the map were forwarded to the departments responsible at the Olomouc city, police, or other administrative authorities for solution, and the process of evaluation of each risk area was recorded. It is apparent that recording and appropriate intervention can result in improved environmental quality to ensure increased safety and thus promote active transport for children to and from schools. By understanding these threats in school neighbourhoods, we can encourage children to choose active modes of transport, leading to improved health and a more sustainable lifestyle.